Emergence of personal knowledge networks in agent-mediated PKM processes: A qualitative analysis in Malaysian context - Ismail S.; Ahmad M.S. (2023)
Personal knowledge networks have been primarily conceived by researchers with regard to the inter-firm knowledge sources between organisations, where networks are informal and personal. Instead of looking at the organisational context, some researchers investigate the intra-firm aspects at personal level of organisational knowledge networks, where knowledge management processes start and end. In a recent study on agent-mediated personal knowledge management (PKM) processes, an interview survey has been conducted to investigate the needs of organisations in tapping the personal knowledge networks among the employees by understanding the processes of managing knowledge at personal level. It also attempts to justify the knowledge sources for agent-mediation that are not only characterised by the usual knowledge repositories and databases, but also the knowledge experts within and outside of an organisation. The survey covers two main industries in Malaysia, which are Service and Education, in which the sampling of experts for respondents is made on these two industries. This paper analyses and discusses the results of this interview survey, to contribute to the domain of agent technology in mediating the human knowledge worker's PKM processes. It then recommends future works in modelling the bottom-up approach of PKM-OKM, where personal knowledge networks manifest the organisational knowledge management with the help of software agents. 2012 IEEE.